P62 A comparison of the relative effects of exposure on FEV1 and FVC in occupational COPD. (12th November 2015) - Macfarlane, JG; Stenton, SC
Abstract : Introduction and objectives: A wide range of occupational exposures to dusts and fumes are known to cause COPD. Little is known about the underlying pathophysiology as few studies have measured gas transfer or included CT scans. It is not known whether the relative degree of small airway disease and emphysema is similar to that seen with smoking or varies by causative agents. The modifying effect on lung function of pneumonoconiosis, that is a feature of several accepted or possible causes of occupational COPD, is also uncertain. Methods: We have reviewed papers investigating exposure-response relationships for FEV1 and FVC to a range of occupational dusts and fumes. We examined the ratio of the slopes of the regression equations relating exposure to FEV1 and FVC for the occupational exposures and for cigarette smoking. Results: We identified 15 papers dealing with exposure to coal mine dust (5 papers), silica-containing dusts (8 papers) and other dusts (2 papers). The relative effects of exposure on FEV1 and FVC are shown in Figure 1, together with the relative effects of smoking on FEV1 and FVC obtained from the same papers. It should be noted that as FEV1 is lower than FVC, an equal reduction in FEV1 and FVC with exposure (ratio = 1) still leads to airflow obstruction. Cigarette smoking had an effect on FEV1 that was approximately twice the effect on FVC. Coal mine dust was associated with a similar ratio of effect though with greater variability. Studies on silica-containing dusts had a more equal effect on FEV1 and FVC. That was also the case for the two studies of non-silica containing dusts (carbon black and potash mining). Conclusions: COPD associated with exposure to silica-containing dusts appears to be associated with a more restrictive abnormality than COPD associated with cigarette smoking and coal dust, possibly because of a modifying effect of associated lung fibrosis.